CHALLENGES OF PROTECTING THE RIGHTS OF CHILDREN AND PARENTS WHEN SEPARATING A CHILD FROM THE FAMILY (EU and comparative law issues and challenges series (ECLIC), 2024)
The right of the child and parents to enjoy each other's company is guaranteed by Article 35 of the Constitution of the Republic of Croatia, Article 8 of the European Convention for the Protection of Human Rights and Fundamental Freedoms, and Article 7 of the EU Charter of Fundamental Rights. However, when parents do not comply with their responsibilities, duties and rights for the proper growth and development of children, there is a threat and/or a violation of the children's personal rights and well-being. If we begin with the understanding that children's personal rights and well-being are of the highest value and are part of the public order, the state must provide their protection, which includes not only the imposition of repressive measures, but also the provision of special care and assistance in preserving the family unit.The paper will provide an outline of the Republic of Croatia's international commitments concerning family law protection measures, as well as obligations emanating from national normative acts. In addition, the constitutional judicial practice and the practice of the European Court of Human Rights will be analyzed to determine whether the state follows its obligations to protect the rights of the child and parents when imposing repressive measures to protect the personal rights and well-being of the child, and de lege ferenda proposals for the improvement of national normative acts, i.e. guidelines for a more consistent application of the existing legal framework in the practice of imposing measures by which a child is separated from the family in accordance with European standards of respect for the right to family life.